Within or Without? How Firms Combine Internal and External Labor Markets to Fill Jobs - Bidwell, Matthew; Keller, JR (Academy of Management Journal, 2014)
We examine which jobs are more likely to be filled by internal mobility (specifically, promotions and lateral transfers) than by hiring. Building on the assumptions of transaction cost accounts of employment, we develop a new theory that focuses on the interaction between the problems of evaluating and integrating external hires, on the one hand, and the incentive costs of failing to promote eligible workers, on the other. These arguments lead us to predict how three specific characteristics of jobs—demands for firm-specific skills, performance variability, and supply of internal candidates—affect how those jobs are staffed. Using seven years of personnel data spanning all jobs from the U.S. offices of a large investment bank, we find that jobs with higher performance variability and a larger grade ratio of junior to senior workers are more likely to be filled by internal mobility. We also find evidence that the effects of performance variability are contingent on the grade ratio, affecting staffing decisions only when the firm does not face strong pressures to promote junior workers in order to maintain incentives. Contrary to expectations, we find no effect for firm-specific skills.